2014
DOI: 10.1115/1.4027310
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Thermohydrodynamic Morton Effect Analysis—Part II: Parametric Studies

Abstract: This paper presents simulation results corresponding with the theoretical Morton effect model explained in Part I, where the 3D finite element models of bearing, shaft, and fluid film are adopted. In addition, it explains how thermal bow induced imbalance force develops in the spinning journal with time and how the vibration level is affected by the thermal bow vector. Shaft asymmetric thermal expansion induced by nonuniform journal heating is simulated, which is one of the unique contributions of this researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As can be seen in Figure 5, a "Jeffcott"-type symmetric rigid rotor supported on the five-pad TPJB was employed as a mechanical model to investigate the rotordynamic bifurcation analysis owing to the pad-pivot friction. The governing equations of motion for the rotor and TPJB pads in the system can be written as: (8) where m J and I p are the rotor mass and pad moment of inertia, respectively; and W s and W d are the static and dynamic loads on the rotor, respectively.…”
Section: Rigid Jeffcott Rotor-tpjb Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As can be seen in Figure 5, a "Jeffcott"-type symmetric rigid rotor supported on the five-pad TPJB was employed as a mechanical model to investigate the rotordynamic bifurcation analysis owing to the pad-pivot friction. The governing equations of motion for the rotor and TPJB pads in the system can be written as: (8) where m J and I p are the rotor mass and pad moment of inertia, respectively; and W s and W d are the static and dynamic loads on the rotor, respectively.…”
Section: Rigid Jeffcott Rotor-tpjb Modelmentioning
confidence: 99%
“…The TPJB's stiffness and damping coefficients, which were modified using the equivalent spring model, were in good agreement with the test results, but showed a very large difference in the journal eccentricity. Suh and Palazzolo [8] developed a three-dimensional high fidelity finite element model for the spherical pivot type TPJB, which can simulate the effect of pivot stiffness. They found that the rigid pivot yields the highest temperature in the lubricant, pad, and shaft, providing the increased thermal expansion and the decreased minimum film thickness ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Panara et al [16] found the phenomenon that synchronous vibration instability of overhung rotor due to viscous shearing within lubricant film in engineering. Suh et al [17,18] suggested that there is a large journal surface temperature difference when the journal whirls in journal bearing. It causes temporary rotor thermal bending and leads to vibration instability of the rotor.…”
Section: Introductionmentioning
confidence: 99%
“…Suh J. [5][6] studied the instability of oil film caused by thermal effects. Pouya Asgharifard-Sharabiani [7] presented the nonlinear model identification of oil-lubricated tilting pad bearings.…”
Section: Introductionmentioning
confidence: 99%